Numerical Analysis of Microring Resonator obtained by Wafer-Bonding Technology - Kusko, M (Institutional Knowledge at Singapore Management University, 2005)
Microring resonators will be one of the most important components of the next generation of optical communications. In this work, we have analyzed from theoretical perspective a new proposed microring resonator structure based on the wafer-bonding technique which implies the vertical coupling between the passive bus waveguide and the active ring resonator. We have investigated the possibility to obtain the monomode operation of the active ring waveguide for certain ring radius values by the selective attenuations of the higher order modes and the obtaining of the desired coupling efficiency by varying the technological parameters like the layers thickness, etching depth, bus waveguide width and the offset (misalignment between the ring and the bus waveguide). Depending on the fabrication method, the misalignment between the ring resonator and the bus waveguide may vary within a significant range. Therefore, we considered a much wider bus waveguide in the coupling region in order to minimise the effects of misalignment.